Kittenhood : blife-size portraits of kittens in their first 12 weeks - Ernhart, Sarah Beth. (New York : Stewart, Tabori & Chang, 2013)
"Kittenhood showcases adorable kittens in life-size photographs taken in the early weeks of their lives. The book itself is oversize at 13 by 11 inches, allowing enough space to bring each of these little ones to life. Twenty-five breeds are captured in engaging photographs, showing all the details that make kittens so irresistible, from their soft, fluffy bellies to their tiny teeth, large eyes, beautiful coloring, and expressive tails. The book features the most popular breeds, including Siamese, tabby,tuxedo, RagaMuffin, Persian, American shorthair, and Oriental shorthair, among others. Kittenhood is a unique gift book for cat lovers everywhere."--Publisher description.
Keywords: Kittens -- Pictorial works; Cats -- Pictorial works; Photography of cats